2019
DOI: 10.1016/j.jand.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Outcomes of a Pilot Randomized Clinical Trial to Increase Cruciferous and Green Leafy Vegetable Intake in Posttreatment Head and Neck Cancer Survivors

Abstract: Background: Higher intakes of cruciferous vegetables (CV) and green leafy vegetables (GLV) in observational studies are associated with improvements in survival and cancer-related biomarkers in patients diagnosed with head and neck cancer (HNC). These results have yet to be corroborated in a randomized clinical trial (RCT). Objective: Determine the feasibility of implementing a 12-week RCT to increase CV and GLV intake in post-treatment HNC survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Originally, 24 participants were recruited, but only 23 are included in this analysis due to missing serum cytokine and carotenoid data for one participant. A detailed description of the pilot study methods and population have been detailed elsewhere [26]. The study was approved by the Institutional Review Board at UAB and University of Illinois Urbana-Champaign (UIUC) and all participants provided written informed consent before initiating study activities.…”
Section: Study Population and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, 24 participants were recruited, but only 23 are included in this analysis due to missing serum cytokine and carotenoid data for one participant. A detailed description of the pilot study methods and population have been detailed elsewhere [26]. The study was approved by the Institutional Review Board at UAB and University of Illinois Urbana-Champaign (UIUC) and all participants provided written informed consent before initiating study activities.…”
Section: Study Population and Proceduresmentioning
confidence: 99%
“…Herein, we report an analysis of data collected as part of a pilot clinical trial in HNC survivors [26]. We investigate blood samples with the objective of characterizing survivors according to DNA methylation signatures in leukocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Crowder et al reported that head and neck cancer survivors were receptive to and adherent of a 12-week intervention including weekly correspondence and counseling from a Registered Dietitian. In this pilot study, the intervention group displayed an mean increase in GLV intake by 5.5 cups and cruciferous vegetables by 3.5 cups per week [36]. Pierce et al investigated the feasibility of a high vegetable diet in breast cancer survivors to prevent recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were randomized to two groups: (1) an attention control group ( n = 12) that received weekly telephone counseling from a registered dietitian nutritionist (RDN) focusing on general healthy eating for cancer survivors while addressing chronic side effects of treatment that might interfere with the ability or desire to eat; or (2) an experimental group ( n = 12) who received the same weekly dietary counseling plus additional goals for consuming 2.5 and 3.5 cups of cruciferous (CV) and green leafy vegetables (GLV) per week, respectively. A detailed description of the study population and intervention methods have been described elsewhere [15]. Briefly, stage I–IV oral, pharyngeal, or laryngeal cancer patients who were > 6 months post-treatment and able to consume at least soft foods orally were recruited via the institutional cancer registry.…”
Section: Methodsmentioning
confidence: 99%
“…However, dietary intervention preferences in HNC survivors are understudied [8, 14]. As such, the objective of this study was to determine dietary intervention preferences and a study program evaluation as reported by post-cancer treatment HNC survivors who previously participated in a pilot dietary intervention trial [15]. Results can inform future frameworks for successful dietary interventions within this patient population and determine acceptability of research testing dietary interventions.…”
Section: Main Textmentioning
confidence: 99%